The conversion of RAS status in metastatic colorectal cancer patients after first‐line biological agent treatment. (20th October 2020) - Arici, Serdar; Hamdard, Jamshid; Sakin, Abdullah; Sengiz Erhan, Selma; Atci, Muhammed Mustafa; Cekin, Ruhper; Saka, Burcu; Köse, Emin; Saydam, Tuba; Geredeli, Caglayan; Cihan, Sener; Bilici, Ahmet
Abstract: Aim: The aim was to investigate the RAS discordance between initial and recurrent metastasectomy specimens in metastatic colorectal cancer (mCRC) patients treated with chemotherapy (CT) plus biological agents in a first‐line setting. Methods: Patients who had been treated with CT plus bevacizumab or cetuximab or panitumumab followed by R0 resection for potentially resectable colorectal cancer liver metastases were scanned. Among these, patients who developed resectable new metastases after a disease‐free interval longer than 6 months were included in the study. We compared the RAS mutation status between the first biopsy and the second metastasectomy specimen. Results: A total of 82 mCRC patients treated with CT plus biological agents in a first‐line setting were included in the study. The first biopsy assessment showed wild‐type RAS tumours in 39 (47.6%) patients and mutant RAS tumours in 43 (52.4%) patients. The mean time for new operable liver metastasis after R0 resection was 15.5 months. In the second metastasectomy specimens, the numbers of wild‐type and mutant RAS tumours were 30 (36.6%) and 52 (63.4%), respectively. The comparison with the first biopsy specimens showed RAS status conversions in 17 (20.7%) patients. Univariate comparison between patients with and without RAS status conversion revealed that grade, pathological T stage, wild‐type RAS tumour and longer biological agent use time in the first‐line treatment were significant factors for RAS conversion. Conclusion: Our results suggest that re‐biopsy is needed for an optimal second‐line treatment decision in mCRC patients regardless of backbone biological agent, especially in patients with wild‐type RAS mCRC.